Mengkaji Tantangan Serta Peluang Peran Penyuluh Agama Katolik dan Moderasi Beragama di Propinsi Kepulauan Riau - Laurensius Dihe Sanga (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
This study aims to examine the challenges and opportunities in the role of Catholic religious instructors related to religious moderation in the Riau Islands Province. Religious moderation has become a crucial issue in maintaining social harmony amidst the pluralism of Indonesian society. The Riau Islands Province, with its diversity of religions and ethnicities, presents unique dynamics in the context of tolerance and coexistence. Catholic religious instructors play an important role in promoting the values of moderation, tolerance, and interreligious dialogue, but they face various challenges, such as limited resources, skills, and policy support. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with Catholic religious instructors, religious leaders, and local communities, as well as document analysis of related religious policies in the region. The study results indicate that the main challenges faced by Catholic religious instructors include limited access to training on religious moderation, and insufficient infrastructure and logistical support in remote areas. On the other hand, there are significant opportunities to strengthen the role of Catholic religious instructors, particularly through interreligious collaboration and increasing understanding of religious moderation values relevant to the local context. The study suggests the need to enhance the competence of religious instructors through continuous training, and to increase synergy between the government and religious institutions to facilitate dialogue and cooperation among religious communities. In this way, the role of Catholic religious instructors can be optimized to support religious moderation and create harmonious religious life in the Riau Islands Province.